Implikasi Hukum Transaksi Jual Beli Tanah tanpa PPAT dalam Konteks Hukum Agraria Indonesia - Arthur Arthur; Hasim Sukamto; Diana Ria Winanti Napitupulu (Jurnal Syntax Admiration, 2024)
Land sale and purchase transactions without involving Land Deed Making Officials (PPAT) often cause various legal problems, because the resulting deeds are considered invalid according to agrarian law in Indonesia. This study aims to analyze the legal consequences of land transactions that are not carried out in front of PPAT and how disputes that arise can be resolved. This study uses a qualitative method with a descriptive approach through interviews with legal practitioners and the study of related documents. The research method used is qualitative with a descriptive approach, where data is obtained through interviews with legal practitioners and analysis of related documents. The results of the study show that transactions carried out without involving PPAT have the potential to harm the parties involved, especially in terms of legal certainty and land ownership rights. In addition, it will be difficult for the acrimonized party to prove ownership in court in the event of a dispute. This study recommends the importance of legal education for the community and the enforcement of appropriate procedures in land purchase and sale transactions, in order to reduce risks and improve the protection of the rights of the parties. In conclusion, land purchase and sale transactions carried out without involving PPAT increase the risk of disputes and legal uncertainty, so legal education and enforcement of land purchase and sale procedures involving PPAT are very important to protect the rights of all parties involved.